(untitled) (Tempo e Argumento, 2021)
This text deals with the way in which the “struggle” for the independence of São Tomé and Príncipe was constituted in an unquestioned narrative – moreover, it was not narrated because it had little to tell and because it was convenient to silence what was known by some and intuited by the islanders meanwhile dispossessed of voice – but with political implications, among them, the acceptance of the dominance of a few over the majority. The enticing disruption of the “struggle”, after 25 April, blurred rationality, eliminated the possibilities of choice and, in the circumstances, contributed to the creation of new dominations, regardless of the joy of the moment of independence and the certainty of the most likely victory of the MLSTP if there had been a referendum or elections on the course of the archipelago. Keywords: São Tomé and Príncipe; colonialism; independence; historical knowledge.